Study of the Corrosion Speed of Nails in Agar- Agar Media - Arwan; Riko Rayhan Radite Putra Wibowo2b; Luki Pratama; A. Bakoh Adi Anggoro; Ilyas Faiz Tsalits (Fakultas Teknik Universitas PGRI Banyuwangi, 2023)
Corrosion events in daily life present their own problems for an industry. Most corrosion phenomena themselves are electrochemical reactions that occur naturally between metals or metal alloys and the environment. This research aims to determine the corrosion rate of nails using agar media. This research was carried out by calculating the corrosion rate using the weight loss method only due to rusting when the sample was submerged for 36 hours, 72 hours and 108 hours on the corrosion rate of iron nails. Based on research results. From the research it can be concluded that the longer the soaking time, the smaller the rate of corrosion caused by the pack. The corrosion resistance of nails is very good because it is less than 0.02 mm/years. During the immersion period of the iron material in the gelatin medium, the corrosion rate was very good because < 1. The results of the research can be concluded that the longer the soaking time, the smaller the corrosion rate caused by the pack. The corrosion resistance of nails is very good because it is less than 0.02 mm/years. During the immersion period of the iron material in the gelatin medium, the corrosion rate was very good because it was < 1.